The Life and Death of de-Baathification - Hazem Saghieh (Revue des Mondes Musulmans et de la Méditerranée)
De-Baathification policies begun in 2003 and abandoned in 2004, were justified essentially in terms of the German and Japanese experiences following World War II. These policies however, emerged from the beginning as forms of revenge, not only against the Ba’ath as a party and system, but also against the "Sunni Triangle" and Arab nationalism. The inability to comprehend the Iraqi situation in its context and above all to distinguish between the Baathist regime and State public services caused widespread counter reactions and led to violence.